Thresholds, encounters : Paul Celan and the claim of philology - Mendicino, Kristina; Zechner, Dominik, 1988- (Albany : State University of New York Press, 2023)
"Explores the various ways in which poetic and philosophical writing meet in texts by, and on, Paul Celan"--
Dis-positions : introduction / Kristina Mendicino and Dominik Zechner -- "In the swell of wandering words" : Celan's "Sprich auch Du" / Michael G. Levine -- A different withness : bearing with the past in Paul Celan's "Engführung" / Simone Stirner -- Flower talk / Jan Mieszkowski -- Poetic involution : Adorno, Celan, nature / Natalie Lozinski-Veach -- Allophony : Celan's Niemandsrosen-Lieder / Michael Auer -- "A chest full of cello boughs" : the sonorous force of writing in deconstructive readings of Celan / Naomi Waltham-Smith -- A limine / Kristina Mendicino -- With -- Paul Celan / Pasqual Solass -- Occupiability (trans. Aida Feng) / Sarah Stoll -- For shame of language / Dominik Zechner -- Poetic approach : Celan's radio essay "Die Dichtung Ossip Mandelstams" / Irina Kogan -- The mimetic desire of translation : reading Celan and Derrida with Girard / Christine Ivanovic.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Celan, Paul -- Criticism and interpretation; Celan, Paul -- Themes, motives; Celan, Paul; German poetry -- 20th century -- History and criticism; Philology; Poésie allemande -- 20e siècle -- Histoire et critique; Philologie; philology; German poetry; Philology; Themes, motives; Criticism, interpretation, etc